EDUCATIONAL VIDEOS ON THE LEVEL OF TEENAGERS' KNOWLEDGE ABOUT THE IMPACT OF EARLY MARRIAGE IN PUBLIC JUNIOR HIGH SCHOOL 1 DEMPAR, KUTAI BARAT REGENCY - Kurniati, Sinta; Masyitah, Gita; Meihartati, Tuti; Hartati, Dwi (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Background: Early marriage is a serious problem in adolescence, the lack of understanding of adolescents due to early marriage is the main factor. It is important to provide effective education, one way is through the use of educational videos. The study aims to determine the influence of adolescent knowledge on the impact of early marriage through educational media in the form of videos. Research purposes: Is there an effect of providing educational videos on the level of knowledge of adolescents about the impact of early marriage at Public Junior High School 1 Dempar, West Kutai Regency. Method: The study used a pre-experimental design, with a one group pre-test -post-test design. The sampling technique used was consecutive sampling with a sample size of 110 respondents. The analysis test used was the Wilcoxon Rank test. Results: The results of the level of knowledge of respondents about the impact of early marriage before being given educational videos were mostly in the less category with 66 (60.0%) respondents, the sufficient category with 17 (15.4%) respondents, and the good category with 27 (24.6%) respondents, while after being given educational videos there was an increase in the majority of respondents having a less knowledge level with 3 (2.7%) respondents, the sufficient category with 34 (31.0%) respondents, and the good category with 73 (66.3%) respondents. There was an effect of providing videos with a p-value of 0.001 p <α (0.05). Conclusion: This study concludes that there is an increase and influence of providing educational videos on the level of knowledge of the impact of early marriage at Public Junior High School 1 Dempar, West Kutai Regency.